2004
DOI: 10.1111/j.1600-0609.2004.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab as treatment for minimal residual disease in hairy cell leukaemia

Abstract: Purine analogues have dramatically improved the outcome of patients affected by hairy cell leukemia (HCL), although complete eradication of disease was achieved in few cases. The purpose of this study was to evaluate the role of Rituximab in eradicating minimal residual disease (MRD) in HCL patients after a pre-treatment with 2-chloro-deoxy-adenosine (2-CdA). Ten patients received four cycles of Rituximab after administration of Cladribrine. Before starting anti-CD20 antibody, two patients were in complete rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…Moreover, results are difficult to interpret because of the heterogeneity of the techniques and samples used for each patient. The low rate of MRD negativity we observe after rituximab (two of nine patients) may also be due to the fact that MRD evaluation was often performed quite early after treatment, whereas previously published data have shown that molecular responses increase over time and are still quite low at 2 and even 6 months [19,14].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, results are difficult to interpret because of the heterogeneity of the techniques and samples used for each patient. The low rate of MRD negativity we observe after rituximab (two of nine patients) may also be due to the fact that MRD evaluation was often performed quite early after treatment, whereas previously published data have shown that molecular responses increase over time and are still quite low at 2 and even 6 months [19,14].…”
Section: Discussionmentioning
confidence: 66%
“…For these patients, MRD was analyzed on a BM or PB sample using either immunophenotyping by flow cytometry or detection of an immunoglobulin heavy chain gene rearrangement by polymerase chain reaction (PCR) [19,20].…”
Section: Minimal Residual Disease Evaluationmentioning
confidence: 99%
“…A different approach would be to evaluate the marrow for MRD at 3 to 6 months after the completion of therapy with cladribine and administer monoclonal antibody only to those patients with evidence of MRD as has been done by Cervetti et al 33 Alternatively, pretreatment features may be identified that would predict the likelihood of relapse, thereby allowing selection of appropriate patients for additional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that PCR of sequences encoding surface IgH using consensus primers was less sensitive than flow cytometry, the latter able to detect below one HCL cell in 10 4 normal cells (24). Capillary electrophoresis after fluorescent PCR using consensus primers allowed detection until one IgH + cell was diluted into 10 5 normal cells (21) and showed that MRD cleared in five of eight with CR, suggesting that rituximab might finally be an agent capable of eradicating HCL. We reasoned that assessing eradication of HCL would require even higher sensitivity PCR tests, previously reported for chronic lymphocytic leukemia and acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Small clinical trials have reported a total of 18 (30%) CRs of 60 HCL patients (17 -20). Of eight HCL patients in CR after rituximab, five proved negative by PCR using consensus primers, a technique sensitive until one IgH-positive cell was diluted into 10 5 normal cells (21). BL22 is a recombinant immunotoxin containing truncated Pseudomonas exotoxin fused to the variable domains of an anti-CD22 monoclonal antibody, which induces CRs in 19 (61%) out of 31 purine analogue-resistant HCL patients (22,23).…”
Section: Hairy Cell Leukemia (Hcl) Is a Clonal Chronic B-cellmentioning
confidence: 99%